Kinetic evaluation of imidacloprid degradation in mice organs treated with olive oil polyphenols extract - Broznić, Dalibor (Array, 2008)
Summary: Imidacloprid is a highly effective insecticide, acting as agonists at the insect nicotinic acetylcholine receptor. Nevertheless, imidacloprid itself or its metabolites could exhibit toxicity in mammals. Imidacloprid biotransformation involves oxidative cleavage, releasing the 6-chloronicotinic acid. Therefore, the concentration of imidacloprid and 6-chloronicotinic acid was used to characterize degradation kinetics and distribution of imidacloprid in mice liver, kidneys and lungs. Additionally, the influence of olive oil polyphenols on imidacloprid metabolism was evaluated. Experimental animals were divided into three groups: control, IMI – imidacloprid treated mice (5 mg/kg) and (IMI + PP) – mice treated with polyphenols (10 mg/kg) for seven days before the administration of imidacloprid. Neither imidacloprid nor 6-chloronicotinic acid could be detected 48 hours after administration in IMI group, while complete degradation in the (IMI + PP) group was accomplished within 24 hours. Significantly higher rate constant and shorter half-life in (IMI + PP) group emphasize that polyphenols may diminish the toxicity of this pesticide